Pengaruh Pariwisata Sendang Gile terhadap Perilaku Anak Usia Sekolah Menengah - Herwanti, Sri Dewi; Fakhri, Moh; Faqih, M. (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2024)
This study aims to analyze the influence of Sendang Gile tourism on the behavior of junior high school students at SMPN 3 Bayan, North Lombok Regency, during the 2022/2023 academic year. Tourism in the Bayan area not only provides economic impacts but also social and cultural consequences, particularly on adolescent behavior. This research employed a descriptive qualitative approach using observation, interviews, and documentation. The results revealed that tourism significantly influenced student behavior, both positively and negatively. Positive impacts included improved communication skills, openness, and enthusiasm for learning foreign languages. Negative impacts involved tendencies to imitate tourist lifestyles that are inconsistent with local norms. Supporting factors included parental, school, and village government support, while inhibiting factors were weak social control and lack of environmental supervision. In conclusion, Sendang Gile tourism plays an important role in shaping student behavior, requiring collaborative efforts among parents, schools, and the community to direct tourism’s influence in a positive direction.